INITIAL RESULTS OF STUDY ON SEDIMENTATION RATE, SEDIMENT SOURCE TO THE HA LONG BAY: EVIDENCE FROM THE 210Pb AND 137Cs RADIOTRACER - Vuong, Bui Van; Liu, Zhifei; Thanh, Tran Duc; Huh, Chih-An; Nhon, Dang Hoai; Ve, Nguyen Dac; Huy, Dinh Van (Vietnam Journal of Marine Science and Technology, 2016)
Ha Long bay is the World Natural Heritage, which annaually attracts a lot of foreign and domestic tourists. Nevertheless, in recent years, the landscape of Ha Long bay is devastated by many negative impacts-the shallowing of the bottom of bay is one of the great negative impacts. How is the shallowing of the bottom of Ha Long bay? What are reasons for the negative impacts? Based on the approach “source-to-sink” combined with results of clay mineral contents, results of 210Pb and 137Cs radionuclides, this study will contribute to clarifying the shallowing of the bottom of Ha Long bay. Results of smectite, illite and smectite/(illite+chlorite) ratios indicated that the sediment in Ha Long bay not only derives from the surrounding region of Ha Long bay but also derives from Red river system. Results of 210Pbex and 137Csex revealed the sedimentation rates in the Ha Long bay have varied between 0.47 - 0.75 cm/year over the last 100 years. It can be divided into four periods: period I (1920 - 1930); period II (1930 - 1960); period III (1960 - 1990); and period IV (1990 - 2011) with the average rate of 0.45 cm/year; 0.66 cm/year; 0.50 cm/year; and 0.85 cm/year respectively. The shallowing of the bottom of Ha Long bay was impacted by human activities such as building reservoirs, mining, urbanization or aquaculture etc.